2020
DOI: 10.1158/2159-8290.cd-20-0057
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment Is Critical for the Maintenance of Cellular States Found in Primary Glioblastomas

Abstract: Tumor microenvironment is critical for the maintenance of cellular states found in primary glioblastomas.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
134
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(141 citation statements)
references
References 37 publications
6
134
1
Order By: Relevance
“…The major non-neoplastic immune cell population in the GBM microenvironment includes cells of the innate immune system called tumor-associated macrophages (TAMs), as well as the stromal cells such as tumor-associated broblasts (TAFs). TAMs and TAFs are of great importance in several aspects of the tumor progression and chemotherapeutic processes of GBM [10]. It's been reported that age-related immune alternations could cause landscape remodeling of the tumor microenvironment and initiate the invasiveness and aggressiveness of tumors, including GBM [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major non-neoplastic immune cell population in the GBM microenvironment includes cells of the innate immune system called tumor-associated macrophages (TAMs), as well as the stromal cells such as tumor-associated broblasts (TAFs). TAMs and TAFs are of great importance in several aspects of the tumor progression and chemotherapeutic processes of GBM [10]. It's been reported that age-related immune alternations could cause landscape remodeling of the tumor microenvironment and initiate the invasiveness and aggressiveness of tumors, including GBM [41].…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular heterogeneity allows the classi cation of these tumors into different molecular subtypes, namely proneural (PN), classical (CL) and mesenchymal (MES) subtypes, among which MES had the poorest outcome [7]. Intercellular heterogeneity, on the other side, contains a series of non-neoplastic cells, including in ltrating and resident immune cells, stromal cells, other glial cells, extracellular matrices (ECM) and other components related to the tumor microenvironment (TME) [10]. This tumor immunology and tumor microenvironment has added another level of complexity to this phenomenon.…”
Section: Backgroundsmentioning
confidence: 99%
“…Furthermore, GBM has been extensively characterized by scRNA-seq providing a detailed baseline for both the transformed populations that co-occur in individual patients and the microenvironment [7][8][9][10][11] . Indeed, single-cell characterization of GBM models has highlighted the importance of the tumor microenvironment in maintaining the phenotypic diversity of malignant cells 12 . We obtained GBM surgical specimens from six patients, generated multiple 500 micron slices, and placed them in short-term culture for drug perturbation (Fig.…”
mentioning
confidence: 99%
“…We found that those GBM patients with higher PHQ-9 and GAD-7 score have signi cantly worse prognosis than their lower scored counterparts. It seems the case that glioblastoma and depressive/anxiety disorder share some common etiological factors, such as in ammation [33,34], neurotransmitter metabolism [35], glutamine [36,37], neural plasticity [38,39], etc. Nevertheless, none of these factors were con rmed by further research.…”
Section: Discussionmentioning
confidence: 99%